Indexing hematological and serum biochemical reference intervals of Himalayan snow trout, Schizothorax esocinus to instrument in health assessment - Reshi, Quseen Mushtaq; Ahmed, Imtiaz; Al-Anazi, Khalid Mashay; Farah, Mohammad Abul (Frontiers in Physiology, 2023)
Schizothorax esocinus is one of the main contributors of food and livelihood in the colder zone of Himalayan region but information on its hematological and serum biochemical reference intervals is not reported yet. The goal of this study was to establish hematological and serum biochemical reference intervals of Schizothorax esocinus from River Jhelum. Data values from a total of healthy 432 adult fish specimens (216 male, 216 female) was recorded. The reference intervals for hematological and serum biochemical parameters of S. esocinus were established using Reference value Advisor v 2.1. Reference intervals for some hematological and serum analytes ranged as: hemoglobin 78.38–116.35 (g/L); white blood cells 10–20 (×109/L); red blood cells 1.30–2.15 (×1012/L); packed cell volume 27.00–39.45 (%); total protein 39.21–61.62 (g/L); albumin 8.20–22.02 (g/L); globulin 27.58–49.55 (g/L); glucose 3.25–7.18 (mmol /L); urea 0.96 – 2.38 (mmol /L); cholesterol 3.80–6.90 (mmol/L). Differences in some blood analytes between the sexes were observed. Significantly (P<0.05) higher levels of hemoglobin (Hb), red blood cell (RBC) count and serum glucose were noted in male as compared to female which, on the other hand, registered higher white blood cell (WBC) count and serum cholesterol (Mann Whitney U test, P<0.05). The work, therefore, provides baseline information on hematological as serum biochemical analytes of this species which holds high commercial importance.